SIT Open Source per la divulgazione e la gestione delle informazioni in ambito naturalistico (GEOmedia, 2018)
The collection of naturalistic data, and their consequent management and organization to allow fruition and analysis, is a fundamental part of the life of a National Park.The Park Autorithy has implemented a suite based on the OS application G3W-SUITE. The framework allow to publish and manage WebGis services directly from cartohraphic project made by QGIS.The geographic portal, named http://biodiversita.parcoforestecasentinesi.it, allow free and rstricted access to the various WebGis services.G3W-SUITE is released on GitHub with Mozilla Public Licence 2.0